Factors Affecting Customer Perception Toward Customer Loyalty of Street Food Hygiene During The Pandemic: A Case of Bangsean, Thailand - Nakpathom, Parinya; Pitchayadejanant, Krittipat; Viet, Minh Nhat; Vivatvani, Vorrapob; Asmaniati, Fetty (Institut Pariwisata Trisakti, 2023)
This research paper focused on the investigation of customer perception in the context of hygienic street food in the case of Bangsean City, Thailand. Three variables have been analyzed in this valuation as follows: food hygiene practice, service and sanitation operation, and street food atmosphere. Regarding research methodology, the authors used a quantitative approach to testify on an Exploratory Factor Analysis (EFA) and Linear Regression Analysis. Particularly respondents were collected by distributing four hundred questionnaires to Thai citizen tourists who had recently visited the town with consumed street food in a place. As a result, indicated that customer perception positively affected customer satisfaction. Simultaneously, customer satisfaction positively affected customer loyalty. Moreover, the finding can be justified by a new persuasive method of contribution for the street food vendors in terms of hygiene conditions, in order that enhances the quality of food, service and sanitation operation advancement, and build-up an atmosphere which are the factors affecting to the customer’s perception. Keywords: Street Food Hygiene, Customer Perception, Customer Satisfaction, Customer Loyalty, Bangsean